Antibacterial Activity of Aerial Part Extracts and Fractions of Ajuga chamaecistus ssp. tomentella - Seyede Nargess Sadati Lamardi; Sara Tahroodi; Mahnaz Khanavi; Reza Hosseini Doust (Tehran University of Medical Sciences, 2017)
The genus Ajuga [Kamafitos] has been used as wound healing in traditional Persian medicine. Recent studies have shown that some species of this plant has antibacterial effects. Methanol 80% and aqueous extract and partition fractions of n-hexane, diethyl ether, and n-butanolic from a methanolic extract of Ajuga chamaecistus ssp. tomentella were evaluated for antibacterial activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa using cup-plate method. Furthermore, (minimum inhibitory concentration) MIC was determined using micro plate method. Gentamicin and vancomycin were used as positive control and methanol 5% was used as negative control. Zone of inhibition (mm) and the MIC (µg/ml) were measured in three times. Based on the results, all extracts and fractions showed antibacterial effect against S. aureus, B. subtilis, E. coli and P. aeruginosa, among them the diethyl ether fraction exhibited the most antibacterial effect against S. aureus (zone of inhibition =18mm) and B. subtilis (zone of inhibition =16.5mm). Also, n-butanolic fraction showed the most antibacterial effect against E. coli (zone of inhibition =16mm) and methanolic extract presented the most antibacterial effect against B. subtilis (zone of inhibition =15mm). S. aureus was the most sensitive (MIC>333µg/ml) and P. aeruginosa was the most resistant (MIC>4000µg/ml) bacteria to the extracts. The above results revealed that most of the extracts and fractions from this plant possess antibacterial activity against micro-organisms specially S. aureus. According to traditional use of Ajuga species as wound healing medicinal plant, it can be used for treatment of various skin infections and possibly reduction of healing time.